Research trends on parasocial interactions and relationships with media characters. A review of 281 English and German-language studies from 2016 to 2020 - Schramm, Holger; Liebers, Nicole; Biniak, Laurenz; Dettmar, Franca (Frontiers in Psychology, 2024)
Parasocial phenomena are among the most popular and best-researched topics in media reception and effects research. The research can now look back on a history of over 65 years and has experienced another significant boom in recent years. Between 2016 and 2020, more studies were published than in the entire previous 60 years (Liebers & Schramm, 2023). This descriptive review builds directly on the seminal review by Liebers and Schramm (2017a, 2019) for the years 1956 to 2015 and is based on 281 English- and German-language studies published from 2016 to 2020. The following three research questions guided the review: How are the studies from 2016 to 2020 positioned in terms of the media contexts examined, the parasocial phenomena investigated, the methods and measurements used and the samples? (RQ1) What has changed in the studies from 2016 to 2020 compared to the studies from 1956 to 2015 in terms of the media contexts investigated, the parasocial phenomena studied, the methods and measurements used and the samples? (RQ2) What substantive perspectives and key insights can be gained from the studies conducted between 2016 and 2020 and what gaps in research can still be observed? (RQ3) The results show, for instance, that the largest proportion of studies from 2016 to 2020 focused on the area of social and new media, on non-fictional characters and amicable forms of parasocial relationships, using surveys and existing measurement instruments or adapted versions of them (RQ1). Compared to the studies from 1956 to 2015, parasocial phenomena are increasingly being researched experimentally, as mediating and moderating factors and using established scales, with a slight increase in the proportion of studies specifically investigating parasocial relationships or relationship breakups (RQ2). The research focus has evolved from film and television to social media and cross-media settings. Most empirical studies of parasocial phenomena still rely on young and predominantly female samples (RQ2). The neglect of negatively valenced parasocial phenomena, comparative cultural perspectives, comparative media perspectives, long-term effects and less educated and older people as samples can still be identified as major research gaps (RQ3) and opens up numerous opportunities for future research.